Geotechnical earthquake engineering handbook : with the 2012 International building code - Day, Robert W. (New York : McGraw-Hill Professional, 2012)
'The latest methods for designing seismically sound structuresFully updated for the 2012 International Building Code, Geotechnical Earthquake Engineering Handbook, Second Edition discusses basic earthquake principles, common earthquake effects, and typical structural damage caused by seismic shaking. Earthquake computations for conditions commonly encountered by design engineers, such as liquefaction, settlement, bearing capacity, and slope stability, are included. Site improvement methods that can be used to mitigate the effects of earthquakes on structures are also described in this practical, comprehensive guide.Coverage includes: Basic earthquake principles Common earthquake effects Earthquake structural damage Site investigation for geotechnical earthquake engineering Liquefaction Earthquake-induced settlement Bearing capacity analyses for earthquakes Slope stability analyses for earthquakes Retaining wall analyses for earthquakes Other geotechnical earthquake engineering analyses Grading and other soil improvement methods Foundation alternatives to mitigate earthquake effects Earthquake provisions in building codes'--
'This one-stop resource--filled with in-depth earthquake engineering analysis, testing procedures, seismic and construction codes--features new coverage of the 2012 International Building Code'--
Includes bibliographical references and index.
Keywords: Earthquake engineering -- Handbooks, manuals, etc; Engineering geology -- Handbooks, manuals, etc